Structural-phase transitions and state function in unstable convective medium - Gushchin, I.V.; Kirichok, A.V.; Kuklin, V.M. (Вопросы атомной науки и техники, 2015)
Convection in a thin layer of liquid (gas) with temperature independent viscosity between poorly heat conducting boundaries is studied within framework of the Proctor-Sivashinsky model. We have shown by numerical simulation of the Proctor-Sivashinsky model that the state with certain topology can be described by the state function, which is the sum of squared mode amplitudes of spatial temperature spectrum. The transitions between these states are characterized by splashes in time-derivative of this function and different meta-stable structures, corresponding to different values of the state function have different visually distinguishable topologies.